Antifungal activities of wood extractives. Issue 3 (June 2017) - Valette, Nicolas; Perrot, Thomas; Sormani, Rodnay; Gelhaye, Eric; Morel-Rouhier, Mélanie
Abstract: Extractives are non-structural wood molecules that represent a minor fraction in wood. However, they are source of diverse molecules putatively bioactive. Inhibition of fungal growth is one of the most interesting properties of wood extractives in a context of wood preservation, crop protection or medical treatments. The antifungal effect of molecules isolated from wood extractives has been mainly attributed to various mechanisms such as metal and free radical scavenging activity, direct interaction with enzymes, disruption of membrane integrity and perturbation of ionic homeostasis. Lignolytic fungi, which are microorganisms adapted to wood substrates, have developed various strategies to protect themselves against this toxicity. A better knowledge of these strategies could help both developing new systems for extractive removal in biomass valorization processes and using these molecules as antifungal agents.